CP-168 Economic impact of clinical pharmacist´s interventions on antimicrobial therapy in critically ill patients. (25th February 2017) - Leache, L; Aquerreta, I; Aldaz, A; Idoate, A; Ortega, A
Abstract : Background: A clinical pharmacist (CP), as part of the healthcare team (HT), can contribute to adequate anti-infective use. Few studies have evaluated the economic impact of CP´s interventions (CPI) in the intensive care unit (ICU), and most consider only drug costs. Purpose: To analyse the economic impact of CPI regarding antimicrobial therapy (AT) in the ICU. Material and methods: We conducted a retrospective analysis of CPI regarding AT in the ICU over a 5 month period. The CP spends 5 hours/day, 5 days/week in the ICU. 33% of CPI are anti-infective related. Information regarding CPI is recorded daily in the hospital´s information system and includes the drug involved, type of intervention, acceptance by physicians and estimated costs (incremental and avoided) as a consequence of the CPI. These costs include changes in drugs, time and products for drug preparations and administration, and the pharmacist's time. To estimate costs (incremental or avoided) we assumed that the change to the recommended and accepted therapy would have happened 2 days later the without CPI (CPI contribute to earlier changes). For sensitivity analysis, we considered that the change would have happened in 1–4 days. The ratio 'avoided cost to invested money' was calculated. Results: 212 interventions were recorded, corresponding to 114 patients. Most frequent types of CPI were: modification of drug dose and/or interval (MD) (50.9%), drug discontinuation (DD) (22.6%), change to a more cost effective administration route (CR) (14.6%), initiate a drug (7.5%) and change to a more cost effective drug (CD) (2.4%). Physicians´ acceptance rate was 97.6%. Over the 5-month period, we estimated a total decrease in costs as a consequence of CPI of €7013 (34.8% decrease), corresponding to €33.1/intervention and €61.5/patient. According to sensitivity analysis, total savings varied from €2779 to €19 011. This estimation included the cost of the CP's time during the studied period (€2859). Therefore, €3.5 were avoided per €1 invested in the CP. Types of CPI associated with greater total savings were (in decreasing order): DD, MD and CR(and per intervention: CD, CR and DD). Conclusion: Having a CP as a member of the HT in the ICU performing interventions related to antimicrobials is economically beneficial. References and/or acknowledgements: Thanks to the pharmacy service. No conflict of interest